Review of electrostatic system parameters, charged droplets characteristics and substrate impact behavior from pesticides spraying - Appah, Samuel; Wang, Pei; Ou, Mingxiong; Gong, Chen; Jia, Weidong (International Journal of Agricultural and Biological Engineering, 2019)
Electrostatic spraying application is adopted in crop protection to prevent pest infestation, to improve product quality and to maximize yield. It involves a superposition of charges to pesticide spray droplets to attract substrate ions at obscured surfaces. The droplets wraparound effect reduces off-target deposition, enhances on-target spray and invariably improves spray efficiency. Electrostatic spraying system works effectively at optimum parameters in combination with charging voltages, application pressures, spraying height regimes, flow rate, travel speed, electrode material, and nozzle orientation. Many combinations of the system parameter settings have been systematically used by researchers for the electrostatic application, but there are unknown specific optimum parameters combinations for pesticide spraying. Since droplets chargeability influences the effectiveness of electrostatic spraying system, the parameters that produce ideal charge to mass ratio determine the functionality of the spraying deposition, retention and surface coverage. This article, therefore, analyses electrostatic system parameters that produce suitably charged droplets characteristics for effective impacting behavior of pesticides on substrates. Increasing applied voltages consequently maximizes charge-mass ratio to optimum and starts declining upon further increase in voltages beyond a critical point. This review further proposes the selection of an optimum electrostatic parameters combination that yields optimum droplets chargeability in pesticide application. Also, it is necessary to investigate the charge property of substrates prior to pesticide application in order to superpose the right opposite charge on spray droplets at rupture time during electrostatic spraying system. Keywords: electrostatic spraying, charged droplets, substrates, deposition, wraparound, charge-mass ratio DOI: 10.25165/j.ijabe.20191202.4673 Citation: Appah S, Wang P, Ou M X, Gong C, Jia W D. Review of electrostatic system parameters, charged droplets characteristics and substrate impact behavior from pesticides spraying. Int J Agric & Biol Eng, 2019; 12(2): 1–9.